Dissociation of intact Escherichia coli ribosomes in a mass spectrometer. Evidence for conformational change in a ribosome elongation factor G complex. - Hanson, C; Fucini, P; Ilag, L; Nierhaus, K; Robinson, C (2003)
We used mass spectrometry to identify proteins that are released in the gas phase from Escherichia coli ribosomes in response to a range of different solution conditions and cofactor binding. From solution at neutral pH the spectra are dominated by just 4 of the 54 ribosomal proteins (L7/L12, L11, and L10). Lowering the pH of the solution leads to the gas phase dissociation of four additional proteins as well as the 5 S RNA. Replacement of Mg(2+) by Li(+) ions in solutions of ribosomes induced the dissociation of 17 ribosomal proteins. Correlation of these results with available structural information for ribosomes revealed that a relatively high interaction surface area of the protein with RNA was the major force in preventing dissociation. By using the proteins that dissociate to probe their interactions with RNA, we examined different complexes of the ribosome formed with the elongation factor G and inhibited by fusidic acid or thiostrepton. Mass spectra recorded for the fusidic acid-inhibited complex reveal subtle changes in peak intensity of the proteins that dissociate. By contrast gas phase dissociation from the thiostrepton-inhibited complex is markedly different and demonstrates the presence of L5 and L18, two proteins that interact exclusively with the 5 S RNA. These results allow us to propose that the ribosome elongation factor-G complex inhibited by thiostrepton, but not fusidic acid, involves destabilization of 5 S RNA-protein interactions.